Trypanosoma cruzi infection: role of wnt signaling in the modulation of fibroblast phenotype and function - Brugo, María Belen (2022)
Fil: Brugo, María Belén. Universidad Nacional de Córdoba. Facultad de Ciencias Quimicas; Argentina.